KAJIAN FILOSOFIS & PROBLEMATIKA HUKUM BISNIS DALAM MEMASUKI PERDAGANGAN INTERNASIONAL - Edi Krisharyanto (Perspektif, 2002)
Trading is a service sector that supports local and internation economics activity. In the international trade system, Indonesia has taken part in the success of Uruguay Round of GATT. The agreement resulted from the Round bound all the participants to follow GATT in every trading activity. There are three principles of GATT: reciprocity, most favored nation (MFN) and transparency, all of which to eliminate trading problem among the countries.